2010
DOI: 10.1677/jme-10-0015
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic regulation of bone

Abstract: On initial inspection, bone remodeling, the process whereby the skeleton adapts through time, appears to be relatively simple. Two cell types, the bone-forming osteoblasts and the bone-resorbing osteoclasts, interact to keep bone mass relatively stable throughout adult life. However, the complexity of the regulatory influences on these cells is continuing to expand our understanding of the intricacy of skeletal physiology and also the interactions between other organ systems and bone. One such example of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 42 publications
2
51
1
Order By: Relevance
“…These findings are in contrast with the widespread (based mainly on animal studies) view that leptin acting primarily through the centrally (hypothalamus and brainstem) mediated pathways suppresses bone formation [14,71,72], but are in accord with some, but not all [34,44,[73][74][75][76], clinical studies that reported a positive association between serum leptin and OC levels [77,78] and with experiments showing that peripheral leptin increases osteoblast proliferation, differentiation and activity, inhibits osteoclast activity and bone resorption, increasing bone mass [79][80][81]. Furthermore, a meta-analysis (59 studies) found that leptin was positively associated with bone mineral density (BMD) and high levels of leptin were predictive of lower risk of fractures [82].…”
Section: Adipokines and Markers Of Hepatic Mineral And Bone Metabolismcontrasting
confidence: 88%
“…These findings are in contrast with the widespread (based mainly on animal studies) view that leptin acting primarily through the centrally (hypothalamus and brainstem) mediated pathways suppresses bone formation [14,71,72], but are in accord with some, but not all [34,44,[73][74][75][76], clinical studies that reported a positive association between serum leptin and OC levels [77,78] and with experiments showing that peripheral leptin increases osteoblast proliferation, differentiation and activity, inhibits osteoclast activity and bone resorption, increasing bone mass [79][80][81]. Furthermore, a meta-analysis (59 studies) found that leptin was positively associated with bone mineral density (BMD) and high levels of leptin were predictive of lower risk of fractures [82].…”
Section: Adipokines and Markers Of Hepatic Mineral And Bone Metabolismcontrasting
confidence: 88%
“…Discovery of the scope and strength of neural influences upon skeletal tissue has been an important advance in bone biology in recent years (Driessler and Baldock, 2010). Further expanding these unique neuro/skeletal relationships, here we identify a novel interaction between the opioid system and bone demonstrating an inhibitory action of dynorphins on skeletal tissue, acting through kappa opioid receptors.…”
Section: Discussionmentioning
confidence: 84%
“…(reviewed in refs (24) and (25) ). Leptin interacts directly or indirectly with these systems, thereby accounting for some of the differential effects reported for leptin in different bone compartments.…”
Section: Discussionmentioning
confidence: 99%